Blending of Cellulose and Chitosan in Alkyl Imidazolium Ionic Liquids. (3rd December 2012) - Kuzmina, Olga; Heinze, Thomas; Wawro, Dariusz
Abstract : The production of cellulose/chitosan blends in alkyl imidazolium ionic liquids (ILs) was studied in this work. Selected organic solvents, such as dimethyl sulfoxide, ethyl acetate, and diethyl ether, were used as cosolvents. The addition of cosolvents decreased the viscosity of cellulose/chitosan solutions in ILs and facilitated the dissolution of polysaccharides, thereby decreasing theE act and polymer aggregates sizes in the solutions. The cellulose/chitosan films were produced from the studied solutions. The presence of one of cosolvent and ILs in the blended films was confirmed by FTIR spectroscopy. The blended film is stronger than pure cellulose film, and the addition of cosolvents has an influence on its mechanical properties.